LC–MS/MS-guided discovery of japonamides C and D, two new cyclohexadepsipeptides, from the Nicotiana tabacum-derived endophytic fungus Aspergillus japonicus TE-739D - Wang, Haisu; Hao, Xianwei; Dong, Chen; Yuan, Xiaolong; Zhang, Peng; Gu, Gan (Frontiers in Microbiology, 2025)
Endophytic fungi belonging to the Aspergillus genus have received substantial attention due to their notable secondary metabolic potential. In this study, chemical investigations using LC–MS/MS-based molecular networking on the endophytic fungus Aspergillus japonicus TE-739D led to the discovery of two new cyclohexadepsipeptides, namely japonamides C (1) and D (2), along with three known cyclodipeptides (3–5). Their structures, including the absolute configurations of the amino acid residues, were elucidated through spectroscopic data analysis and an optimized Marfey’s method. The newly discovered compounds, japonamides C (1) and D (2), were screened for broad-spectrum cell proliferation inhibitory activity against 20 different human cell lines. The results indicated that both compounds displayed broad-spectrum antiproliferative activity against MKN-45, HCT116, TE-1, 5,637, CAL-62, and A-637 cells, with inhibition rates ranging from 55.0 to 72.3%. Moreover, the antibacterial activity of compounds 1–5 against two Gram-positive bacteria and two Gram-negative bacteria was also evaluated.